2020
DOI: 10.12669/pjms.36.covid19-s4.2636
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Attitude of Undergraduate Medical Students towards 2019-novel Corona virus

Abstract: Objective: To assess the knowledge, awareness and attitudes of medical students towards recently discovered coronavirus disease-19 (COVID-19). Methods: This was a cross sectional study conducted on medical students in CMH Lahore Medical College,(LMC), Institute of Dentistry (IOD). A questionnaire containing demographic information, 14 knowledge and eight attitude items was completed by 384 participants. Results: Overall, >90% people were aware about the etiology, mode of transmission and possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
79
2
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 17 publications
21
79
2
17
Order By: Relevance
“…In our finding, around 91.2% of Ethiopian Population had heard about Novel coronavirus at the time of the study. It is comparable with a study conducted in Pakistan in which more than 90% of medical students had heard about the disease (Ikhaq et al 2020). Furthermore, this finding is in line with a study conducted in Nepal in which 91.6 % of population aware all the clinical features of Coronavirus (Vaidya et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our finding, around 91.2% of Ethiopian Population had heard about Novel coronavirus at the time of the study. It is comparable with a study conducted in Pakistan in which more than 90% of medical students had heard about the disease (Ikhaq et al 2020). Furthermore, this finding is in line with a study conducted in Nepal in which 91.6 % of population aware all the clinical features of Coronavirus (Vaidya et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…Africa's already fragile health systems, coupled with a high burden of would cost the continent greatly. The speed with which countries can detect report and respond to outbreaks can be a reflection of their wider institutional capacity (Ikhaq, Riaz et al 2020, Olapegba et al 2020. The threat of COVID-19 to health systems in Africa can be compared with a metaphor which says "the eye of the crocodile"; which means in the lake, only the eyes of the crocodile is visible on the surface while the rest of the body is immersed in water.…”
Section: Introductionmentioning
confidence: 99%
“…Students from MBBS and BDS stream were aware of facts like the causative factors for the COVID-19 disease (95.6%) and the type of virus causing this infection (92.7%). This was in accordance with a recent study from Pakistan [25], where majority of students, (97.4%) were aware about the causes and the viral nature of the disease and also with another study from India, which showed 92.7% of the participants' had good knowledge. 26 Our study has shown that only 71% of students were aware about the mode of transmission of this virus, which is lesser compared to the results from a similar study among students, where 97.4% of them knew about the transmission modes and the signs and symptoms of the disease.…”
Section: Resultssupporting
confidence: 91%
“…Students from MBBS and BDS stream were aware of facts like the causative factors for the COVID-19 disease (95.6%) and the type of virus causing this infection (92.7%). This was in accordance with a recent study from Turkey and Pakistan [17,21], where majority of students, (97.4%) were aware about the causes and the viral nature of the disease and also with another study from India, which showed 92.7% of the participants' had good knowledge. [22] Our study showed that only 71% of students were aware about the mode of transmission of this virus, which is lesser compared to a similar study from India among students, where 91% knew about the transmission modes and the signs and symptoms of the disease.…”
Section: Resultssupporting
confidence: 91%